Can hunter’s local ecological knowledge be used in management of multi-ungulate systems? : a combination of local ecological knowledge and scientific knowledge to add a finer resolution to current management strategies - Pettersson, Sandra (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2021)
Management and conservation of wildlife populations are generally based on scientific knowledge (SK) and monitoring to establish reliable information. The information gathered and presented from SK is interpreted by individuals who can have different ways of interpreting the same type of information. To increase the validity and range of opinions, other types of knowledge can be incorporated with SK. There are a variety of non-scientific types of knowledge that can be used depending on the research question, such as local ecological knowledge (LEK), local knowledge (LK), traditional ecological knowledge (TEK) and indigenous local-, and traditional knowledge (ILK/ITK).